THE ROLE OF WORK MOTIVATION AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL COMMITMENT: CASE STUDY OF GENERATION X AND Y TAXI DRIVERS IN PT. Z - Karen Febriena Andini van den Broek; Clara Moningka; Yulius Fransisco Angkawijaya (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2017)
The gap between generation X and Y becomes a challenge to avoid turnover in organizations. Taxi companies have experienced high turnover due to the emergence of the phenomenon of online taxi. One way to retain employees is to increase organizational commitment. Organizational commitment can be influenced by motivation and organizational culture. This study focuses on the effect of motivation and organizational culture on organizational commitment of generation X and Y taxi drivers. This research is a quantitative research, using regression and two-way ANOVA to 184 respondents in Jakarta, Bogor, Depok, Tangerang, dan Bekasi. The result of analysis shows that motivation significantly influences organizational commitment of taxi drivers of both generations (p < .05). Motivation and organizational culture simultaneously affect the organizational commitment of the generation X driver (p < .05) but does not affect generation Y (p > .05). There is no difference in organizational commitment based on organizational culture on both generations. In this study, age and tenure is an important factor affecting organizational commitment. There is no difference in organizational culture because it is affected by task identity. Task identity can be a powerful factor in predicting organizational commitment.